Legal aspects of ways to monetize rights in the computer games industry - N. Yu. Andreev; V. V. Arkhipov; A. A. Vasiliev; Yu. V. Pechatnova (Правоприменение)
The subject. The authors attempt a legal analysis of several forms of monetization of rights to computer games.The purpose of the article is the legal qualification of donations, crowdfunding, loot boxes as means of monetization.The research methodology includes general scientific methods of analysis and synthesis, as well as specific scientific methods of comparative law and formal legal analysis.The scientific problem of the article lies in the existing contradiction between the rapid development of the computer games market and the state of modern legal science in terms of scientific understanding and regulation of the entertainment industry.The main results, scope of application. There are two main forms of public funding in the gaming industry: (1) donations; (2) crowdfunding. Donations are more common for streamers, crowdfunding for computer developers. Donat is money sent without the condition of reciprocity. In recent years, crowdfunding has become a common way to attract investments. The purchase of a digital (or physical) copy of a game is the acquisition of the right to use (access) a computer game. Therefore, the funds we transfer are investments. We become beneficiaries of the published product. As a result, the developer will have to pay taxes on the funds raised. A loot box is a virtual item – a random set of additional features.The process of loot distribution is similar to a game of chance: players choose the level of need for a thing. Lootbox, despite the deceived expectations of the player, still brings some benefits to the player. In other words, the player pays a few dollars and expects to receive something of value in return, but the amount of winnings can be both large and small. In this regard, it seems that the loot box is a classic win-win lottery. Therefore, loot boxes should not be equated with gambling, otherwise the gaming industry could respond by referring to the need to include lotteries (and insurance) as gambling. At the same time, the similarity of several elements indicates that there is always a risk of turning a computer game into gambling.Conclusions. There are a number of ways to monetize the material incentives for players. These methods include donations, funds received in the course of crowdinvesting, as well as loot boxes. Donations are an intermediate phenomenon between donation and payment. For individuals, income from donations will not be taxed if there is no consideration. Also, sometimes donations should be understood as funds from crowdinvestments, which developers sometimes collect to create the next game. These funds, in most cases, should still be treated as developer income, not donations. The boundary between the payment of in-game property and gambling is the phenomenon of loot boxes, which should be qualified as a win-win lottery.